Comparison of Postoperative Changes in Inflammatory Marker Levels Between Transthoracic and Transcatheter Device Closures of Atrial Septal Defects in Children - Hong,Zhi-Nuan (2020)
Abstract Objective: To explore the postoperative changes in inflammatory markers in children who underwent device closure of an atrial septal defect (ASD) via a transthoracic or transcatheter approach. Methods: The experimental and clinical data were retrospectively collected and analyzed for a total of 53 pediatric patients between September 2018 and December 2018. According to the different treatments, 19 patients who underwent transthoracic device closure were assigned to group A, and the remaining 34 patients who underwent a transcatheter approach were assigned to group B. Results: All patients were successfully occluded without any device-related severe complication. Compared with the preoperative levels, the postoperative levels of most inflammatory cytokines in both groups were significantly increased and reached a peak on the first day after the procedure. The level of postoperative inflammatory cytokines was significantly lower in group B than in group A. In addition, there was no significant difference in procalcitonin before and after the transcatheter approach. Conclusion: Systemic inflammatory reactions occurred after transthoracic or transcatheter device closure of ASDs in pediatric patients. However, these inflammatory reactions were more significant in patients who underwent a transthoracic approach than in patients who underwent a transcatheter approach.